Isw1 chromatin remodeling ATPase coordinates transcription elongation and termination by RNA polymerase II. - Morillon, A; Karabetsou, N; O'Sullivan, J; Kent, N; Proudfoot, N; Mellor, J (2003)
We demonstrate that distinct forms of the yeast chromatin-remodeling enzyme Isw1p sequentially regulate each stage of the transcription cycle. The Isw1a complex (Iswlp/Ioc3p) represses gene expression at initiation through specific positioning of a promoter proximal dinucleosome, whereas the Isw1b complex (Iswlp/Ioc2p/Ioc4p) acts within coding regions to control the amount of RNA polymerase (RNAPII) released into productive elongation and to coordinate elongation with termination and pre-mRNA processing. These effects of Isw1b are controlled via phosphorylation of the heptad repeat carboxy-terminal domain (CTD) of RNAPII and methylation of the chromatin template. The transcription elongation factor Spt4p antagonizes Isw1p and overcomes the Isw1p dependent pausing of RNAPII at the onset of the elongation cycle. Overall these studies establish the central role played by Isw1p in the coordination of transcription.